The effect of semantic reversibility of agent-target of transitive utterances on utterance structure in Bisindo Yogyakarta - Dewi, Linda Yusfita; Anjarningsih, Harwintha Y. (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2024)
The flexibility of utterance structure can be influenced by semantic factors. At this level, structures can vary in terms of the positions of the constituents, namely subject, predicate, or object. To see how far semantics plays a role in the flexibility of structures, this research aims to investigate how the semantic reversibility of agent-target influences the structure of the resulting BISINDO Yogyakarta signs. The data source for this research was video-recorded signs that had been transcribed into utterances. The data collection instrument used was a collection of pictures that was used to stimulate deaf individuals to produce signed utterances. The results showed that there were differences in the resulting structure. (1) Non-reversible utterance structures tended to produce single-clauses with various patterns dominated by SPO and SOP structures. This diversity was predominantly influenced by the classification of targets, appropriate hand movements, and the omission of the agents. Meanwhile, reversible stimuli tended to produce two structures, namely single-clauses dominated by SPO and multi-clauses dominated by SPO P. The multi-clause structure was the structure that dominated reversible utterances. The complexity of the structure of this reversible content was characterized by an agent-target indexical description, and the involvement of actions/expressions of action targets. This proved the notion that the indexical description found in almost all multi-clause structures was the preference of deaf individuals in avoiding potential ambiguity between agent-target. Just like spoken languages universally, sign languages such as BISINDO in the Yogyakarta region and BISINDO in the Jakarta region also shared linguistic features.